Pengaruh Likuiditas dan Profitabilitas terhadap Agresivitas Pajak dengan CSR sebagai Variabel Intervening - NOVITA ADIYANI; RANANDA SEPTANTA (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2017)
The purpose of this study is to know and provide empirical evidence of the influence of liquidity, profitability, and corporate social responsibility to the tax aggressiveness of property and real estate firms listed on the Stock Exchange, and to know and provide empirical evidence of the influence of liquidity and profitability to corporate social responsibility on listed property and real estate firms On BEI. The research method used by writer is quantitative approach. The sampling technique uses the purposive sampling. Data collection methods used are literature study and documentation study. Data processing using SPSS program version22. The result of the research shows that liquidity does not partially effect on tax aggressiveness, profitability partially influence on tax aggressiveness, liquidity and profitability influence simultaneously to tax aggressiveness, liquidity and profitability do not influence partially to corporate social responsibility, and Corporate social responsibility have no effect Partially to tax aggressivenes.